Synthesis, structure, cytotoxic and antioxidant properties of 6-ethoxy-4-methylcoumarin - Celikezen, F. C.; Orek, C.; Parlak, A. E.; Sarac, K.; Turkez, H.; Tozlu, Ozlem Ozdemir (Elsevier, 2020)
Coumarins have a wide usage area in medicinal applications. It is known that the design and synthesis of new coumarin derivatives are performed to prepare new drugs in many laboratories. The aim of the study was to synthesize 6-ethoxy-4-methylcoumarin and detect its chemical and biological properties for the first time. 6-ethoxy-4-methylcoumarin was synthesized using Pechmann method. Atomic orbital (GIAO) H-1 and C-13 NMR chemical shift values in the ground state were calculated and Density Functional Method (DFT) was applied with the 6-311++G (d, p) basis set to determine chemical properties. 6-ethoxy-4-methylcoumarin was applied to cultured blood samples at various concentrations (10-400 mg/L) for determining biological activity. 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide (MTT) and lactate dehydrogenase (LDH) release assays were used to evaluate cytotoxic effect. In addition, total antioxidant capacity (TAC) and total oxidative status (TOS) were examined to determine antioxidant properties. The results showed that theoretical vibrational frequencies and chemical shift values were close to experimental values. Moreover, 6-ethoxy-4-methylcoumarin showed a slight cytotoxic effect at dose of 200 mg/L and exhibited an antioxidant activity at 25 mg/L concentration without changing oxidative status at all of doses. (c) 2019 Elsevier B.V. All rights reserved.
Keywords: Coumarins; DFT; NMR; Vibrational spectra; Cytotoxic; Antioxidant